WITTGENSTEIN´S METAPHYSICS OF THE INNER AND THE OUTER - M.R.M. Ter Hark (Daimon)
In the very same manuscript in which Wittgenstein, in the last two years of his life, writes about colours and about certainty, he also writes about the concepts of the inner and the outer, the other minds problems and the problem of pretending. The latter remarks, although very original, are still unpublished; in this article they are examined in detail. The thesis defended is that Wittgenstein carries out a radical reversal of the traditional picture of our knowledge of other minds according to which the uncertainty and unpredictability of the outer has to be explained by the inner. Wittgenstein wants to give an analysis of our knowledge of other minds which goes beyond the distinction between the inner and outer. The uncertainty and unpredictability is a consequence of the fact that our psychological concepts are based upon the indefiniteness of situations in which we talk about other minds. This factual way of living and not a metaphysically hidden mind explains the uncetainty. It is argued that in a very interesting way Wittgensteins thoughts about the inner and the outer are an application of his remarks about certainty and doubt.